Between Knowing and Doing: Examining Mental Health Literacy, Stigma, and Social Support in Professional Help-Seeking Among College Students - Cempaka Putrie Dimala; Dinda Aisha; Puspa Rahayu Utami Rahman; Haryanti Mustika (Islamic Guidance and Counseling Journal, 2026)
In the context of increasing mental health concerns among university students, understanding professional help-seeking behavior has become increasingly important. This study examined the relationships among mental health literacy, self-stigma, stigma of mental illness, social support, and professional help-seeking behavior among Indonesian college students experiencing psychological difficulties. A quantitative cross-sectional survey was conducted with 408 participants recruited through purposive sampling. Data were analyzed using JASP version 0.19.1, applying a regression-based model to examine direct, mediating, and moderating effects. Mental health literacy was tested as a mediator, while social support was examined as a moderator. The results indicated that mental health literacy was positively associated with professional help-seeking behavior. Stigma of mental illness was positively related to both mental health literacy and help-seeking, whereas self-stigma was not significantly associated with either variable. Mediation analysis showed that mental health literacy partially mediated the relationship between stigma of mental illness and help-seeking, but not between self-stigma and help-seeking. Social support did not significantly moderate the relationships between stigma variables and help-seeking behavior. These findings suggest that mental health literacy may represent one contributing factor associated with professional help-seeking among university students. However, given the cross-sectional design and modest explanatory power of the model, the results should be interpreted with caution. Future research is needed to further examine the underlying mechanisms of help-seeking behavior in this population.